A Case of Acute Myeloid Leukemia (FAB M2) with Inversion 16 Who Presented with Pelvic Myeloid Sarcoma - Mustafa Çakan; Ahmet Koç; Kıvılcım Cerit; Süheyla Bozkurt; Rabia Ergelen; Irmak Vural (Hindawi Limited, 2014)
Acute leukemias are the most common childhood cancer in all age groups. Acute myeloid leukemias (AML) constitute about 15-20% of acute leukemias. Fatigability, pallor, fever, and bleeding are the most common presenting symptoms of AML. Hepatosplenomegaly and lymphadenopathy are commonly encountered during physical examination. In rare instances eruptions due to skin involvement and localized tumor masses (myeloid sarcoma) may be found. Myeloid sarcoma is especially seen in AML-M2 subtype. By cytogenetic analysis, in AML-M2 subtype t(8;21) is often seen and it is more probable to find inversion 16 in AML-M4Eos subtype. Herein, we present a 15-year-old girl whose initial symptom was abdominal pain for three days and her pathological sign was a large abdominal mass which was verified by imaging studies and diagnosed as myeloid sarcoma by biopsy. On bone marrow examination, she had diagnosis of AML-M2 and by cytogenetic analysis inversion 16 was positive. She was treated with AML-BFM 2004 protocol and she is being followed up in remission on her ninth month of the maintenance therapy.